Successive Refinement Relaying Strategies in Coded Wireless Multicast Networks - Ho, J.; She, J.; Pin-Han Ho (2011 IEEE International Conference on Communications (ICC), 2011)
This paper demonstrates effective strategies for reducing the end-to-end distortion in a decode-and-forward relay network, where a coded wireless multicast/broadcast system utilizes a successively refinable source along with superposition coding (SPC) at the channel to provision large-scale multimedia services. Exploiting the nature of the successive refinement of source information, where enhancement layer data refines the coarse-resolution base layer into full resolution, the proposed framework relays successive refinable information with reduced distortions through a few proposed strategies. Promising results are justified with a practical measure of perceived receiver quality known as end-to-end distortion (EED). Formulations are derived to investigate the impact to distortion when subject to varying fading channel conditions when receivers utilize successive-interference cancellation (SIC) in decoding the SPC broadcast channel. It is concluded that the relaying of solely the enhancement layer information is a more effective way to reduce distortion among other strategies, which has neither been apparent nor discovered from any previous literature.